Using an Institution Platform of E-Learning in English Language Teaching (ELT) Process at ITB AAS Indonesia - Fitria, Tira Nur (International Journal of Computer and Information System (IJCIS), 2024)
E-learning relies on technology. It requires hardware, software, and network infrastructure. Most e-learning environments today are Web-based, so they can be accessed via Web browsers (using HTTP) over a TCP/IP network such as a university or campus network. The objective of this research is to describe the implementation and to find the strengths and weaknesses of the institution's platform of e-learning in ITB AAS Indonesia. This research is descriptive qualitative research. The result analysis shows that ITB AAS Indonesia has an e-learning system that can be accessed at https://itbaas.ac.id/elearning/. The learning process may be governed or managed by a system based on LMS (Learning Management System). The implementation of online English teaching by using e-learning consists include planning, implementation, and evaluation. In preparing English language teaching, the lecture follows instructions for creating materials. Before uploading material, the English lecturer prepares the material file that he/she wants to upload, fills in all material identities (title of the material, choice of courses, choice of class, material content) then uploads material files. In the implementation of English Language Teaching, the English lecturer prepares the media of video conferencing in online learning. The English lecturer carries out online learning by using Zoom meetings and YouTube Live Streaming. In evaluation, the English lecturer can evaluate by giving the mid-term and final semester tasks in the e-learning platform. The e-learning system in ITB AAS Indonesia has advantages, of course, it also has disadvantages. Therefore, the process of improving the e-learning application is still required and needs to be improved for the success of the teaching and learning process.